Identification of Burkholderia pseudomallei Genes Induced During Infection of Macrophages by Differential Fluorescence Induction - Jitprasutwit, Siroj; Jitprasutwit, Niramol; Hemsley, Claudia M.; Onlamoon, Nattawat; Withatanung, Patoo; Muangsombut, Veerachat; Vattanaviboon, Paiboon; Stevens, Joanne M.; Ong, Catherine; Stevens, Mark P.; Titball, Richard W.; Korbsrisate, Sunee (Frontiers in Microbiology, 2020)
Burkholderia pseudomallei, the causative agent of melioidosis, can survive and replicate in macrophages. Little is known about B. pseudomallei genes that are induced during macrophage infection. We constructed a B. pseudomallei K96243 promoter trap library with genomic DNA fragments fused to the 5’ end of a plasmid-borne gene encoding enhanced green fluorescent protein (eGFP). Microarray analysis showed that the library spanned 88% of the B. pseudomallei genome. The recombinant plasmids were introduced into Burkholderia thailandensis E264 and promoter fusions active during in vitro culture were removed. J774A.1 murine macrophages were infected with the promoter trap library and J774A.1 cells containing fluorescent bacteria carrying plasmids with active promoters were isolated using flow cytometric-based cell sorting. Candidate macrophage-induced B. pseudomallei genes were identified from the location of the insertions containing an active promoter activity. A proportion of the 138 genes identified in this way have been previously reported to be involved in metabolism and transport, virulence or adaptation. Novel macrophage-induced B. pseudomallei genes were also identified. Quantitative reverse-transcription PCR analysis of 13 selected genes confirmed gene induction during macrophages infection. Deletion mutants of two macrophage-induced genes from this study were attenuated in Galleria mellonella larvae, suggesting roles in virulence. B. pseudomallei genes activated during macrophage infection may contribute to intracellular life and pathogenesis and merit further investigation toward control strategies for melioidosis.